Potensi Scopoletin sebagai Agonis Reseptor Transferin 2 untuk Pengembangan Terapi Anemia Defisiensi Besi - Asti Swari Paramanindita; Dono Indarto; Balgis Balgis (Faculty of Medicine Universitas Sebelas Maret, 2018)
Introduction: Iron Deficiency Anemia (IDA) is caused by imbalance between iron intake and iron loss in blood circulation. Increased hepcidin level plays an important role in the etiology of IDA. Normally, expression of hepcidin protein is controlled by three different pathways, one of them is interaction between holo Transferin (Holo-Tf) and Transferrin Receptor 2 (TfR-2). Recently, Indonesian herbal plants have widely been used as herbal medicine but there is no active compound that can activate TfR-2 for IDA therapy. The aim of this study was to explore phytochemicals derived from Indonesian herbal plants to interact with TfR-2.Methods: The study was a bioinformatics study with a molecular docking method. The SWISS-MODEL software was used to make TfR-2 protein modeling because the molecular structure of TfR-2 remains unknown. Holo-Tf was used as a standard ligand and obtained from Protein Data Bank with PDB ID 1SUV. All Indonesian phytochemicals which (1) registered at HerbalDB (2) had a three-dimensional molecular structure at PubChem (3) met Lipinski’s Rule of Five criteria were used in this study. AutoDock Vina 1.1.2 was used to analyze the binding affinity which was in kcal/mol. Phytochemical-TfR-2 binding complexes were visualized by using Chimera 1.10rc and or Pymol 1.7.Result: The docking scores of holo-Tf modification with TfR-2 were -6,4±0,1 kcal/mol at Arg466 and -3,4±0,1 kcal/mol at Arg689 respectively. Interaction of modification holo-Tf and TfR-2 was observed not only at Arg466 and Arg689 but also with Asp642 and Ile682. Docking scores of scopoletin were -7,1±0,1 kcal/mol at Arg466 and -5,4±0,1 kcal/mol at Arg689. Scopoletin could interact with TfR-2 at Arg466, Arg689, and Leu630 residues.Conclusions: Computationally, scopoletin is a potential TfR-2 agonist. In future studies, in vitro assay will be used to evaluate the agonist effect of scopoletin in TfR-2.